ANALISIS KUALITAS PELAYANAN DI KANTOR KELURAHAN PASANGKAYU KABUPATEN MAMUJU UTARA - Gamal, Mohamad Saleh (Katalogis, 2018)
The purposes of this study were to determine service quality at Pasangkayu Subdistrict Office North Mamuju Regency. The research was qualitative research with inductive data analysis with 5 (five) informants comprising Pasangkayu Subdistrict officials and the people as major sources. Data analysis technique used by the researcher was descriptive data analysis, with the findings thatservice quality at Pasangkayu Subdistrict Officehad not been having good quality. It was seen from several aspects, namely: (a) Timeliness of service,including timeout; (b) Accuracy of service; (c) Easinessin providing service, namely support facilities such as computers that were still fewer in number; (d) Convenience in obtaining services relating to the place of service, parking area, information availability, and others; (e) Other supporting attributes, such as air-conditioned waiting rooms.